Studi Kebutuhan Kuantitas Dan Kualitas SDM Untuk Sektor-Sektor Unggulan Di Kapet Seram-Maluku - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
ABSTRACT Over the last a decade, there has been increased attention to the economy of the East-Indonesia Region (KTI), arising particularly from an awareness of the existing serious am balance in inter-regional development. In order to overcome this irnbelance, the policy of developing 13 areas for an integrated economic development (KAPET) has been adopted to meet and resolve the challenges facing the East-Indonesia Region. By using a map of workers productivity and the elasticity index of employment opportunities as well as a tinier trend analysis, it is possible to identib, the needs for Inman resources in terms of quantity and quality, and to make an evaluation of the potential factors that will enhance the quality of human resources. The evaluation of the quantity and quality of human resources is based on a projection of the needs for human resources according to sectors, elasticity, and productivity. The objectives of the research are follows: 1) To ident the potentialities of the speciality sectors (i.e plantation and fishery) in Scram as an effort to enhance the capability of human resources